English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Without a calculator step by step please. So that means the 2/3 and 1/2 are 2over3 and 1over2 as the division in the head is impossible.

Thanks.

2006-09-16 09:33:39 · 13 answers · asked by Anonymous in Science & Mathematics Mathematics

13 answers

(8^1/2)^2/3=8^1/3=2
4^-3=1/4^3=1/64
so(8^1/2)^2/3*4^-3=2/64=1/32

2006-09-16 09:42:28 · answer #1 · answered by raj 7 · 2 0

( 8 ^ 1/2) ^ 2/3 * 4 ^ -3

(8 ) ^ (1/2)*(2/3)*(1/4^3)
(8) ^ (1/3) * (1 / 64)
(2) ^ (1 / 64)

to use your calculator :
press 1 / 64 and save your result
press 2 then X^y your saving , You will get the result
If you inverse it you will get 32
as the correct answer is 1/32

2006-09-16 19:53:45 · answer #2 · answered by shady 3 · 1 0

8^1/2 is root 8.

Then, root 8 taken to the 2/3 power is the cube root of root 8, squared, which is just the cube root of 8, which is just 2.

So the left hand side is 2. Multiply that by 1 over 4^3, which is 1 over 64.

You are left with the final answer, 1/32.

2006-09-16 16:42:39 · answer #3 · answered by Link 5 · 1 0

(8^1/2) ^ 2/3 * (4^-3) = (8^1/3) * (1/4^3) = 2 * (1/2^6) = 1/2^ 5 = 1/32 ...

understood the algebraic rules of exponents involved here?

2006-09-16 16:45:44 · answer #4 · answered by m s 3 · 2 0

= 8^[(1/2)*(2/3)] * 4^-3 =8^(1/3) * 4^-3= 8^(1/3) * 1/[4^3] = 2*(1/64)=1/32 = 0.03125

2006-09-16 16:50:25 · answer #5 · answered by nospamcwt 5 · 0 1

okay this means the Square root of Square root of 8 all cubed times 1 over 4 cubed. Just look at it that way

2006-09-16 16:41:52 · answer #6 · answered by mastap425 3 · 0 2

well a little hint
16= 2^4=2*2*2*2
and
2=16^1/4

2006-09-16 16:37:45 · answer #7 · answered by mee 1 · 0 2

(8^(1/2))^(2/3) * (4^(-3))

8^((1/2) * (2/3)) * (1/(4^3))

8^(2/6) * (1/64)

8^(1/3) * (1/64)

2 * (1/64)

2/64

ANS : (1/32)

2006-09-16 18:18:45 · answer #8 · answered by Sherman81 6 · 3 0

(8^1/2)^2/3=8^1/3=2
4^-3=1/4^3=1/64
so(8^1/2)^2/3*4^-3=2/64=1/32

2006-09-16 16:42:38 · answer #9 · answered by Michi 3 · 1 1

that is 8^(1/2*2/3)*4(-3)
=8^(1/3)*4(-3)=(2^3)^1/3*4^(-3)=2^(3*1/3)*2^(-6)=2*2^(-6)=2^(-5)
But one thing I don`t get:
it`s (1/2)^2/3
Or (8^1/2)^2/3
Good luck

2006-09-16 18:14:18 · answer #10 · answered by ioana v 3 · 0 2

fedest.com, questions and answers